Heat transport modeling of the dot spectroscopy platform on NIF. (28th February 2018) - Farmer, W A; Jones, O S; Barrios, M A; Strozzi, D J; Koning, J M; Kerbel, G D; Hinkel, D E; Moody, J D; Suter, L J; Liedahl, D A; Lemos, N; Eder, D C; et al.
Abstract: Electron heat transport within an inertial-fusion hohlraum plasma is difficult to model due to the complex interaction of kinetic plasma effects, magnetic fields, laser-plasma interactions, and microturbulence. Here, simulations using the radiation-hydrodynamic code, HYDRA, are compared to hohlraum plasma experiments which contain a Manganese–Cobalt tracer dot (Barrios et al 2016 Phys. Plasmas 23 056307). The dot is placed either on the capsule or on a film midway between the capsule and the laser-entrance hole. From spectroscopic measurements, electron temperature and position of the dot are inferred. Simulations are performed with ad hoc flux limiters of f = 0.15 and f = 0.03 (with electron heat flux, q, limited to fnT 3/2 / m 1/2 ), and two more physical means of flux limitation: the magnetohydrodynamics and nonlocal packages. The nonlocal model agrees best with the temperature of the dot-on-film and dot-on-capsule. The hohlraum produced x-ray flux is over-predicted by roughly ∼11% for the f = 0.03 model and the remaining models by ∼16%. The simulated trajectories of the dot-on-capsule are slightly ahead of the experimental trajectory for all but the f = 0.03 model. The simulated dot-on-film position disagrees with the experimental measurement for all transport models. In the MHD simulation of the dot-on-film, the dot is strongly perturbative, though the simulation predicts a peak dot-on-film temperature 2–3 keV higher than the measurement. This suggests a deficiency in the MHD modeling possibly due to the neglect of the Righi–Leduc term or interpenetrating flows of multiple ion species which would reduce the strength of the self-generated fields.